Perbandingan Tingkat Kecemasan pada Siswa yang Terpapar dan Tidak Terpapar Pornografi di SMA X Kota Medan - Rara Rizana; Nanda Sari Nuralita (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Anxiety is an unpleasant feeling, such as excessive worry, fear, and helplessness, which can interfere with daily activities.helplessness, which can interfere with daily activities. In Indonesia,anxiety is ranked as the second highest mental disorder. One of the triggering factor is exposure to pornography, which is now easily accessed by children and adolescents through technological developments. Indonesia ranks third in global pornography access. Research shows that pornography addiction can increase the risk of anxiety by up to 13.5% in adolescents aged 18 years and above. This exposure affects the brain, mental and behavior of children and adolescents. This study used an analytic design observational design with a cross-sectional study approach. The sample consisted of 207students of SMA X Medan City who were selected using the Probability Sampling method with Simple Random Sampling technique.method with Simple Random Sampling technique. Primary data were collected through an online questionnaire online using Google Form.Hasil: Respondents were dominated by students aged 17 years old (60.5%) and the majority were female (67.1%). Level of level of mild anxiety was the most dominant, both in students who were exposed to pornography (24.3%) and those not exposed (32.4%). Statistical analysis statistical analysis showed a significant difference in anxiety levels between students exposed to pornography with those not exposed (P = 0.000; P < 0.05). There is a significant difference in anxiety levels between students exposed to and not exposed to pornography in SMA X Medan City. This finding highlights the importance of prevention and intervention efforts against pornography exposure in exposure to pornography in adolescents to reduce the risk of anxiety.